Study of the prescribing pattern for antihypertensive drugs used in pregnancy at a tertiary care center - Baranwal, Satyam; Prajapati, Narendra; Joshi Joseph, Jishi; Parihar, Narendra Bheemraj; Kulshreshtha, Shabdika (International Journal of Research in Medical Sciences, 2025)
Background: One of the most common health problems encountered during pregnancy is hypertension, which remains to be an important factor to the morbidity and death of both the mother and the fetus. The aim of the study was to examine the antihypertensive medication prescribing practices in tertiary care hospital. Methods: This cross-sectional observational study involved 150 prescriptions written for pregnant women with primary essential hypertension at the Geetanjali medical college and hospital's gynecology inpatient department in Udaipur, Rajasthan. This study was conducted over six months of period enlisting 150 patients. Pregnant woman of more than 18 years of age and diagnosed with hypertension during pregnancy were willing to participate in the study were included. Results: Out of 150 patients, the mean age of the patients was 29.97±5.59 years; with a minimum age of 18 years. Among them 13% were from 1st trimester, 9% were from 2nd trimester and 78% were from 3rd trimester. The prescribing pattern of antihypertensive drugs includes monotherapy and combinations therapy. In the current research, the prescribing pattern of antihypertensive drugs was based on the efficacy and safety profile in the pregnancy. Conclusions: According to the current study, the safest treatment for hypertensive urgency and chronic hypertension is a tablet containing labetalol and magnesium sulphate (MgSO4). If the hypertension is detected in the early stages of pregnancy are treated with less medication.